Review: Effect of the combined application of edible coatings and osmotic dehydration on the performance of the process and the quality of pear cubes. (26th September 2021) - Rodriguez, Anabel; Soteras, Mario; Campañone, Laura
Summary: The objective of the present work was to evaluate the combined effect of the application of edible coatings (sodium alginate and low methoxyl pectin) and different osmotic dehydration conditions (sucrose solution: 40 and 60 °Brix, temperatures: 20 and 40°C and times: 1, 2, 4, 8 and 16 h) on pear cubes (water loss, solid gain, performance ratio, the total colour differences, mechanical properties, phenolic content and sensory analysis). The results indicated that samples coated with low methoxyl pectin and treated under 60 °Brix for 16 h at both temperatures (20 and 40°C) presented the best process performance. Statistical analysis showed that the application of the coatings resulted in greater firmness and stiffness of the pear cubes at the end of osmotic dehydration. Besides, alginate coating best preserved the phenolic content (31.4%) than uncoated (26.04%) and pectin‐coated (20.77%) ones. However, total colour differences were not improved with the use of edible coatings (alginate or pectin). In terms of quality, the samples coated with both hydrogels had good overall acceptability by the evaluators and good mechanical properties. However, further studies are required to decrease the difference in colour and leaching of bioactive compounds in pear cubes due to the osmotic dehydration treatment. Abstract : Osmotic dehydration of pear cubes. Effect of coatings on the process performance.